High-sensitivity pressure sensor based on fiber Mach–Zehnder interferometer. (13th September 2017) - Wu, Yue; Xu, Yao; Yang, Yuguang; Jin, Wenxing; Jiang, Youchao; Shen, Ya; Jian, Shuisheng
Abstract: In this paper we propose and experimentally demonstrate an optical fiber structure sensor based on a Mach–Zehnder interferometer for pressure measurement. The fiber sensor is composed of a single-mode-no-core-single-mode structure, a section of capillary pure silica tube and refractive index matching fluid (RIMF). As the pressure decreases, the sealed air in the tube expands and the liquid level of the RIMF increases, which causes a wavelength shift of the interferometer. The measurement of the pressure variation can thus be achieved by monitoring the wavelength shift. The experimental results agree well with the numerical simulation, and a maximum pressure sensitivity of 266.6 nm M p a − 1 is achieved experimentally. Furthermore, the proposed fiber sensor has the potential to obtain higher sensitivity by enlarging the length of the air cavity.